No Time for College? An Investigation of Time Poverty and Parenthood. (2nd November 2018) - Wladis, Claire; Hachey, Alyse C.; Conway, Katherine
ABSTRACT: Postsecondary outcomes are significantly worse for student parents even though they earn higher GPA's on average. This study used institutional records and survey data from a large urban U.S. university to explore whether time poverty explains this trend. The results of regression and KHB decomposition analysis reveal that students with preschool-aged children have a significantly lower quantity and quality of time for college than comparable peers with older or no children, and that time spent on childcare is the primary reason for this difference. Both quantity and quality of time for education had a significant direct effect on college persistence and credit accumulation, even when controlling for other factors. Thus, greater availability of convenient and affordable childcare (e.g. increased on-campus childcare, revised financial aid formulas that include more accurate estimates of childcare costs) would likely lead to better college outcomes for students with young children.